THE MILITARY EXPENDITURE IN THE CONDITIONS OF GROWING GEOPOLITICAL RISKS AND CHANGES IN THE NATURE OF INTERNATIONAL CONFLICTS - SOKHATSKYI, Oleksandr (Scientific journal «World of Finance», 2020)
Introduction. In the context of growing geopolitical tensions, the expansion of conflict zones and changes in the nature of modern international conflicts, the question of determining the amount of military spending is relevant, both from the standpoint of sufficiency, which will protect its borders and security at any time, and from the standpoint of reasonableness to prevent negative macroeconomic effects, first of all, deterioration of social conditions for the population. Therefore, the basis for solving this problem is, first of all, rethinking the essence of international conflicts and the peculiarities of their manifestation in modern conditions, the study of components of military spending, as well as their role in ensuring defense capabilities in new realities.The purpose of the article is to clarify the essence of military spending in the context of changing the nature of modern international conflicts to develop scientific approaches to determining their scope and structure.Methods. Methods of analysis and synthesis, comparison and generalization in the study of the essence of military expenditures and clarification of their components are used in the article.Results. The analysis of modern conflicts and wars in the world allowed to reveal the characteristic features of their manifestation, to characterize modern conflicts as "hybrid" and to define them as asymmetric wars, involving not only classical political and military methods and tools for their resolution, but also non-traditional ones. such as information, economics, sociology, etc. Ambiguity in the interpretation of the nature and structure of military spending by domestic and foreign researchers, international organizations (UN, NATO, IMF) and world-renowned research institutes dealing with war and peace has been clarified. It is proposed to treat military expenditures as an important component of defense and security expenditures associated with the development of the military organization of the state to fulfill the tasks of military doctrine. In order to ensure the transparency of military spending in open economies, it is proposed to allocate in the cost structure the costs of international activities aimed at maintaining peace on the planet.Perspectives. Further research on military spending should be conducted from the standpoint of elucidating their impact on the main macroeconomic indicators of the state.